Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.7324/jabb.2023.99265
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal variation in phytochemical, physicochemical, and morphological aspects of Justicia adhatoda L. plant growing wildly in Western Himalayas

Abstract: Fluctuations in environmental circumstances with varying altitudinal gradients account for variations in plants. This study was performed to scrutinize the impact of varying altitude on medicinal plant, namely, Justicia adhatoda L. for 2 consecutive years. The phytochemical, physicochemical constituents, and morphological aspects of Justicia adhatoda L. were studied and statistically compared. Significant variations were observed among plant height, crown spread, branches, leaves, inflorescence, carbohydrates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 86 publications
0
0
0
Order By: Relevance
“…There is more herbivory pressure at lower altitude that is why plant produces more alkaloids as a defence against herbivory, therefore the alkaloids often decrease with the increase in altitude [34,35]. Similarly, Večeřová et al [32] noted the along with the altitude, the terpenoid content showed a decreasing trend.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…There is more herbivory pressure at lower altitude that is why plant produces more alkaloids as a defence against herbivory, therefore the alkaloids often decrease with the increase in altitude [34,35]. Similarly, Večeřová et al [32] noted the along with the altitude, the terpenoid content showed a decreasing trend.…”
Section: Discussionmentioning
confidence: 95%
“…Similar study done by Thapliyal and Shukla [33] noted a similar result in the Garhwal Himalayan region that there is decrease in alkaloid content with increase in altitude. There is more herbivory pressure at lower altitude that is why plant produces more alkaloids as a defence against herbivory, therefore the alkaloids often decrease with the increase in altitude [34, 35]. Similarly, Večeřová et al [32] noted the along with the altitude, the terpenoid content showed a decreasing trend.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation